THE USE OF YOUTUBE VIDEO BY NON-ENGLISH MAJOR STUDENTS FOR SPEAKING SKILLS - Carolinaliwati Carolinaliwati; Wahyuningsih Usadiati; Misrita Misrita (Cakrawala Indonesia, 2021)
This study was conducted to investigate the use of social media especially YouTube by students the Non-English Major of the Faculty of Economics at the University of Palangka Raya. It was also to see the impact of using social media especially YouTube to improve their speaking ability. The study design of this study was descriptive qualitative. Fifteen students of the Faculty of Economics were selected as participants to speak in front of a handphone camera with the topics already prepared. Five online meetings were done to know their progress. The Semi-structured interview was also done to collect the supporting data of deeper information needed. The result showed that the use of social media especially YouTube gave a high impact on the speaking ability of Non-English Major students as seen from their video and deep information from the interview. However, there was various resistance dealing with the efforts to increase their speaking ability, they are psychological factors (lessmotivated, not confident),environment factor (the relationship with their environment), linguistic factors (finding references, vocabulary selection, speaking style, and gesture). The use of social media especially YouTube might make the students feel easier in overcoming the various resistance to improve speaking ability.